Combined therapy for epistaxis by hereditary hemorrhagic teleangiectasia: A 3-year follow up study on 45 patients. Issue 8 (August 2017) - Papaspyrou, Giorgos; Hecker, Dietmar; Linxweiler, Maximilian; Schick, Bernhard; Al Kadah, Basel
Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a mutilating disease associated with the majority of patients with recurrent epistaxis episodes. The aim of this study was to present a single institution experience with patients treated for nasal epistaxis using a combination of Nd:YAG laser and argon plasma coagulation (APC) vs Nd:YAG laser alone, with a minimum follow-up of 3 years. 45 patients (21 men, 24 women) aged from 15 to 84 years with the diagnosis of HHT were treated in the Department of Otolaryngology, Head and Neck Surgery in Homburg/Saar between 10/2002 and 10/2012 because of epistaxis, using a combination of Nd:YAG laser and APC or Nd:YAG laser alone. The observation period ranged from 36 to 120 months. 15 patients were treated with Nd:YAG laser alone and 30 patients with combined Nd:YAG laser and APC. A revision was necessary in three patients (20%) in the Nd:YAG laser group and in nine (33.3%) patients in the combined group. The difference between revision rates after the two therapy forms was not statistically significant ( p  = 0.492). Bipolar coagulation was additionally applied in 33 patients. There was no statistically significant difference ( p  = 1.00) in revision rates between patients who were additionally treated with bipolar coagulation and those who did not receive bipolar coagulation as part of their treatment. No case of postoperative septal perforation was observed. Nd:YAG laser therapy remains an established option for treating treat epistaxis in HHT patients.